Propuesta de diseño de un producto turístico, para la asociación agropecuaria Manuel Freile Barba La Magdalena parroquia de Angochagua en la provincia de Imbabura - Aldás Aguilar, Katherine Lorena (2021)
The objective of the research was to design a tourist product to take advantage of the tourist potential of the Hacienda La Magdalena located in the city of Ibarra, Imbabura province, to strengthen the development of the productive and tourist capacities of the sector. Different bibliographic sources were consulted from various authors to complete the theoretical support of the conceptual framework. A methodological procedure was developed in which the phases and stages of the research process were structured according to the design of the tourism product, beginning with a situational diagnosis of the area for which information was collected from primary and secondary sources through interviews. Directed authorities and executives of the sector of the study area as a second phase, a market study was carried out in which the existing supply and demand was characterized and the market segment to whom it is directed, through the application of a survey of the population economically active in the city of Ibarra, the design of a tourist product was obtained through the technical projection that aimed to structure and define the model under which the design of the tourist product was made, and as a fourth phase the feasibility analysis corresponding to the evaluation of the project regarding its viability and financing In which we proceed to develop a technical study detailing the elaboration of the product, in which the costs were determined, verifying the viability and profitability of the proposal.